Is total muscle strength related to pelvic floor muscle strength in young women? - Oliveira, Thaís Passos de; Amaral, Maria Teresa Pace do; Scudeller, Tânia Terezinha; Vieira, Wesley de Oliveira; Dourado, Victor Zuniga; Zanetti, Miriam Raquel Diniz (ABCS Health Sciences, 2024)
Introduction: The intravaginal examination is an important part of the pelvic floor muscle (PFM) functional assessment. However, women sometimes refuse to submit to this procedure due to being embarrassed. This justifies the investigation of other alternatives of evaluation that could contribute to the treatment of pelvic floor disorders. Handgrip strength (HGS) provides an approximation of overall muscle strength, strongly associated with functionality, and this could be indirectly linked to the pelvic floor musculature. Objective: To verify whether there is a correlation between PFM strength and HGS. Methods: This is an observational study that evaluated 51 young women who filled out a clinical evaluation form and were submitted to pelvic floor evaluation, using the Modified Oxford Scale, Peritron® perineometer, and HGS (Saehan® dynamometer). For the perineometer and handgrip strength test, three repetitions of the maximum contraction were performed, considering the average of the attempts for analysis. Student’s t-test and Pearson’s coefficient were used to determine the correlation between variables, considering significance <0.05. Results: The participants were normotrophic, with a mean age of 23.14 ± 3.14 years, most were undergraduate students and physically active. The correlation coefficient between handgrip and pelvic floor musculature strength was 0.21 with a confidence interval of -0.07 to 0.46 and a significant value of 0.137. Conclusion: Pelvic floor muscle strength had a weak positive association with HGS. Therefore, it is not possible to state that women who have satisfactory HGS have a strong pelvic floor.